Podcast as Road Safety Education Media for Adult Drivers in Indonesia: Development and Effectiveness Using Uses and Gratifications - Azzah Ula Nabillah Yoni; Brasie Pradana Sela Bunga Riska Ayu; Hanendyo Putro (Sakura Digital Nusantara, 2026)
This study developed a podcast titled